Comparing absorbed doses and radiation risk of the α-emitting bone-seekers [223Ra]RaCl2 and [224Ra]RaCl2 - Lassmann, Michael; Eberlein, Uta (Frontiers in Medicine, 2023)
[223Ra]RaCl2 and [224Ra]RaCl2 are bone seekers, emitting high LET, and short range (<100μm) alpha-particles. Both radionuclides show similar decay properties; the total alpha energies are comparable (223Ra: 28 MeV, 224Ra: 26 MeV). From the mid-1940s until 1990, [224Ra]RaCl2 has been used for treatment of different bone and joint diseases with activities of up to approximately 50 MBq [224Ra]RaCl2. In 2013 [223Ra]RaCl2 obtained marketing author-ization by the FDA and by the European Union for the treatment of metastatic prostate can-cer with an activity to administer of 0.55 MBq per kg body weight for six cycles. For intravenous injections in humans a model calculation using the biokinetic model of ICRP67 shows a ratio of organ absorbed doses coefficients (224Ra:223Ra) between 0.37 (liver) and 0.97 except for the kidneys (2.27) and blood (1.57). For the red marrow as primary or-gan-at-risk, the ratio is 0.57. The differences are mainly caused be the differing half-lives of the decay products of both radium isotopes. Both radionuclides show comparable DNA dam-age patterns in peripheral blood mononuclear cells after internal ex-vivo irradiation. Data on the long-term radiation-associated side effects are only available for treatment with [224Ra]RaCl2. Two epidemiological studies followed two patient groups treated with [224Ra]RaCl2 for more than 25 years. One of them was the “Spiess study”, a cohort of 899 juvenile patients who received several injections of [224Ra]RaCl2 with a mean specific activity of 0.66 MBq/kg. Another patient group of ankylosing spondylitis patients was treated with 10 repeated intravenous injections of [224Ra]RaCl2, 1 MBq each, one week apart. 1,471 of these patients were followed-up in the “Wick study”. In both studies, an increased cancer mortality by leukemia and solid cancers was observed. Similar considerations on long-term effects likely apply to [223Ra]RaCl2 as well since the bio-kinetics are similar and the absorbed doses in the same range: However, this increased risk will most likely not be observed due to the much shorter life expectancy of prostate cancer patients treated with [223Ra]RaCl2.